The Parental Wage Gap and the Development of Socio-Emotional Skills in Children - Paul Hufe (CESifo GmbH, 2024)
Converging labor market opportunities of men and women have altered the economic incentives for how families invest monetary and time resources into the skill development of their children. In this paper, I study the causal impact of changes in the parental wage gap (PWG)—defined as the relative difference in potential wages of mothers and fathers—on children's socio-emotional skills. I leverage administrative and survey data from Germany to create exogenous between-sibling variation in the PWG through a shift-share design. I find that decreases in the PWG do not affect children's socio-emotional development as measured by their Big Five personality traits and externalizing/internalizing behaviors. This null effect can be rationalized by the offsetting effects of the PWG on monetary investments, i.e., more disposable household income that is increasingly controlled by mothers, and time investments, i.e., a substitution from in-home maternal care to informal childcare.
Keywords: J13; J16; J22; J24; 330; gender gaps; skill development; parental investments